First person - Jocelyn Wessels (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Jocelyn Wessels is first author on 'Medroxyprogesterone acetate alters the vaginal microbiota and microenvironment in women and increases susceptibility to HIV-1 in humanized mice', published in DMM. Jocelyn conducted the research described in this article while a Postdoctoral Fellow in Dr Charu Kaushic's lab at McMaster University, Hamilton, Canada. She is now a Postdoctoral Fellow in the lab of Dr Nicholas Leyland at McMaster University, investigating women's reproductive health, in particular reproductive microbiotas.